(untitled) (Bangladesh Journal of Nuclear Medicine, 2017)
Introduction: Bone mineral density (BMD) is an important and measurable risk factor for osteoporotic fractures. Many studies showed higher bone mineral density and lower incidence of fracture in rural population compared to urban population. But all these studies were done in developed countries and very few studies were found in developing countries. This study was carried out to determine the bone mineral density (BMD) in women of both urban and rural dwellers and to evaluation the rate of occurrence of osteoporosis in these two groups. Method: A total 376 women with age range 35 to 85 were analyzed and divided in two groups. Group I rural (n204) and group II urban (n- 172), who were studied at two different Nuclear Medicine centers of Dhaka with different problems specially for low back pain and joint pain. Bone mineral density of lumbar spines (L2-L4) in anterior-posterior position and hip were measured using the Dual Energy X-Ray Absorptiometry-DEXA (Norland XR36). The T- scores were calculated and results were compared between rural and urban women. The history of physical activity, dietary intake of calcium, smoking habit, number of parity and socio-economic condition was also compared with BMD. Results: The mean T score of lumber spines in rural group was -2.31±1.10 and in urban group was -1.78±1.03. The hip of rural group showed mean T score -3.11±1.09 and urban group -3.02±1.09. Mean bone mineral density was lower in rural women than urban but statistically no significant difference was observed between the two groups (P <0.01 and P <0.02 respectively). In rural group 39.2 % cases showed osteoporosis in lumbar spines and 76.4% cases in hip. In comparison the urban group revealed osteoporosis in lumbar spines in 22.7% cases and in hip 40.9% cases. Conclusion: This study revealed lower bone mineral density in rural women than urban in our study population but this difference is statistically not significant. Bangladesh J. Nuclear Med. 18(1): 39-42, January 2015